Parthenolide reduces gene transcription of prosurvival mediators in U937 cells - Mohammadi, S.; Zahedpanah, M.; Nikbakht, M.; Shaiegan, M.; Hamidollah Ghaffari, S.; Nikugoftar, M.; Rahmani, B.; Hamedi Asl, D. (Experimental Oncology, 2017)
In acute myeloid leukemia (AML) the functional abnormalities of osteopontin (OPN), NF-kB, PI3K/AKT/mTOR/PTEN pathway or β-catenin have been considered. Aim: To analyze the response of U937 cells to parthenolide (PTL) through the involvement of expression of OPN protein, RelB, AKT1, mTOR, PTEN and β-catenin genes. Materials and Methods: The U937 cells were treated with PTL at concentrations of 4 μM (IC25) or 6 μM (IC50) and with OPN siRNA for MTT assay and colony forming assay. Western blot analysis using antibodies against OPN was performed with lysates of PTL-treated cells. Quantitative real-time polymerase chain reaction was performed using primers for OPN siRNA, RelB, AKT1, mTOR, PTEN and β-catenin. Results: PTL reduces OPN protein level and down-regulates RelB mRNA in U937 cell line. Suppression of OPN with siRNA increases the cytotoxic effects of PTL. Also, mRNA expression of AKT1, mTOR, PTEN, and β-catenin decreases with PTL or OPN siRNA. Conclusion: Sensitivity of U937 cells to PTL can be associated with the reduction in expression of prosurvival mediators.